The World Bank Annual Report 2003 : Volume 2. Financial Statements and Appendixes - World Bank (Washington, DC, 2013)
The World Bank Annual Report for 2003, reviews the strategy and action pursued by the Bank, based on the Strategic Framework, and Strategic Directions (and Management Action Plan), focused on meeting the development challenges embodied in the Millennium Development Goals (MDGs). To this end, the Bank sharpened its policies, programs, and instruments to support its central mission of reducing poverty, through improved performance monitoring, and management, and improved harmonization of operational policies, procedures, and practices among donors. The Bank also considered other issues, such as its role in the reconstruction of Iraq, the introduction of the grants component in the 13th Replenishment of the International Development Association (IDA), the Operation Evaluation Department's (OED) review of the Heavily Indebted Poor Countries (HIPC) Initiative, and, market access for exports from developing countries. Methods for combating terrorism, and money laundering were also considered during the period under review. The document presents thematic (and regional) perspectives based on two pillars - poverty reduction and economic management - and how to invest in people, towards an environmentally, and socially responsible growth, that supports private sector development, infrastructure development, financial management, and, promotes appropriate legal and judicial systems. The second Volume presents the financial statements for the period July 1, 2002 to June 30, 2003, reporting development activities (loans, guarantees, and other activities), including liquidity management, funding resources, and financial risk management.